Analisis Pengaruh Jenis Air Terhadap Pembusukan Daging Sapi Untuk Memperkirakan Waktu Kematian Seseorang - Irab, Imelda Margaretha; Yen, Liauw Djai; Hartono, Budiman; Antoni, Marcel (Universitas Kristen Krida Wacana, 2026)
Decomposition is a natural process that occurs as soon as the physiological functions of the body cease, at a rate that is influenced by the condition of the body and the environment in which it is located. This study is a descriptive experimental study with a cross-sectional approach that aims to describe the effect of different types of water media, namely fresh water, brackish water, and sea water, on the process of beef spoilage. Air media was used as a comparison control group. The results showed that beef spoilage took place fastest in brackish water media, followed by fresh water, sea water, and slowest in closed air media. Decomposition in closed air media is inhibited due to low humidity, which triggers desiccation and natural mummification. The remaining connective tissue underwent slower decomposition due to the structural stability of collagen which is more resistant to enzymatic degradation. Different types of media significantly affected the rate of beef spoilage, in the order of fastest in brackish water, followed by freshwater, seawater, and slowest in closed air. This finding shows that the old rule of thumb does not always apply, because the rate of spoilage is more determined by environmental characteristics, especially salinity, pH, and water activity that affect the process of autolysis and tissue degradation.